VDTNsim: a simulation tool for vehicular delay-tolerant networks - Soares, V.N.G.J. (2011)
“Copyright © [2010] IEEE. Reprinted from 15th IEEE International Workshop on Computer-Aided Modeling Analysis and Design of Communication Links and Networks.(IEEE CAMAD 2010) ISBN:978-1-4244-7634-3. This material is posted here with permission of the IEEE. Internal or personal use of this material is permitted. However, permission to reprint/republish this material for advertising or promotional purposes or for creating new collective works for resale or redistribution must be obtained from the IEEE by writing to pubs-permissions@ieee.org. By choosing to view this document, you agree to all provisions of the copyright laws protecting it.”